If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + -1) = 5y + 4 Reorder the terms: 6(-1 + y) = 5y + 4 (-1 * 6 + y * 6) = 5y + 4 (-6 + 6y) = 5y + 4 Reorder the terms: -6 + 6y = 4 + 5y Solving -6 + 6y = 4 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -6 + 6y + -5y = 4 + 5y + -5y Combine like terms: 6y + -5y = 1y -6 + 1y = 4 + 5y + -5y Combine like terms: 5y + -5y = 0 -6 + 1y = 4 + 0 -6 + 1y = 4 Add '6' to each side of the equation. -6 + 6 + 1y = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 1y = 4 + 6 1y = 4 + 6 Combine like terms: 4 + 6 = 10 1y = 10 Divide each side by '1'. y = 10 Simplifying y = 10
| 20x+4=6x+4 | | -4(y+1)=0 | | 20x+4=8x+18 | | 4x^2-12x+9=equation | | 2/3x-5/3x | | 4(y+3)=2y+20 | | 3(6)-3(-4)+10(-2)=10 | | 30=5d-3d | | -2.24n=-12.168 | | x-12=x/10 | | 7x-1=8x+2 | | X-3-3x=3(1+x) | | y^4+12y^2+36=0 | | n/-15=5.3 | | 5(2x+6)=55 | | 1.6=4y+20.4 | | 2cos(x)-3x=0 | | 3x+4=9.5 | | n/14.3=-5 | | -0.166666666667= | | 0.5(y+8)=2(y-1) | | 7+8q=7q | | H=-16t^2+24t+40 | | -2x-1=2x+15 | | n/-12.168=-2 | | z+iz+1=0 | | 12(n+8)=132 | | 10(x+3)-9x-4=x-5+3 | | 4x-15=7x-60 | | (7x+15)=8x | | 2(x-4)=35 | | 3/r=12/17 |